Low-coherence enhanced backscattering (LEBS) for bioimaging. - Lim, Noreen Yixuan. (2012)
Coherent backscattering of light (CBS) is a well-established phenomenon in optics. Conventionally, CBS method is used in fields like astronomy and studies of crystalline structures. CBS phenomenon is observable experimentally as a distinct sharp peak superimposed on a diffused background in the backscattering direction. One key obstacle of using CBS method to probe biological tissues is its extremely narrow cone width.